How do mammalian transposons induce genetic variation? A conceptual framework. (14th January 2013) - Akagi, Keiko; Li, Jingfeng; Symer, David E.
Abstract In this essay, we discuss new insights into the wide‐ranging impacts of mammalian transposable elements (TE) on gene expression and function. Nearly half of each mammalian genome is comprised of these mobile, repetitive elements. While most TEs are ancient relics, certain classes can move from one chromosomal location to another even now. Indeed, striking recent data show that extensive transposition occurs not only in the germline over evolutionary time, but also in developing somatic tissues and particular human cancers. While occasional germline TE insertions may contribute to genetic variation, many other, similar TEs appear to have little or no impact on neighboring genes. However, the effects of somatic insertions on gene expression and function remain almost completely unknown. We present a conceptual framework to understand how the ages, allele frequencies, molecular structures, and especially the genomic context of mammalian TEs each can influence their various possible functional consequences. Editor's suggested further reading in BioEssays Evolution of eukaryotic genome architecture: Insights from the study of a rapidly evolving metazoan, Oikopleura dioica Abstract